Maternal and neonatal outcomes following Kielland's rotational forceps delivery. (16th November 2010) - Josephs, KS; Denison, FC; Akolekar, R; Cooper, ES; Stock, SJ
Abstract : Background: There has been a decline in the use of Kielland's rotational forceps for malpositions, associated with reports that their use results in increased complications. However, most of these studies date from more than 20 years ago, and there is a lack of recent data regarding maternal and neonatal outcomes following Kielland's rotational forceps delivery (KRFD). Aim: To describe maternal and neonatal outcomes of KRFD, to compare maternal complications with those of other modes of delivery, and to examine whether operator experience affects maternal outcome. Methods: Retrospective review of KRFD performed in the Simpson Centre for Reproductive Health in Edinburgh between 2001 and 2007 (n=735). Results: Overall numbers of neonatal complications were small. There were no perinatal deaths, but 1.8% (13/735) of neonates had a complication that could be attributable to traumatic delivery (10 nerve palsies, 1 corneal abrasion, 1 fractured clavicle, 1 subarachnoid bleed). 37/735 (5.0%) of women had anal sphincter injury and 6.8% (50/735) postpartum haemorrhage of more than 1000 ml. These complication rates were higher than after spontaneous vaginal delivery (p>0.05) but not significantly different from rates following other operative vaginal delivery. Junior registrars had an 8.1% rate of anal sphincter injury in comparison to the consultant rate of 2.1% (p=0.07). Conclusion: In contrast to previous studies that found unacceptable rates of neonatal injury, the low incidence here suggests there is still a place for Kielland's forceps. In order to draw definitive conclusions about their safety and efficacy long-term outcomes and maternal satisfaction need to be investigated in larger studies.